2021
DOI: 10.1080/2162402x.2021.1908010
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Mechanisms of Response or Resistance to Immune Checkpoint Inhibitors by Analyzing Cell-Cell Communications in Tumors Before and After Programmed Cell Death-1 (PD-1) Targeted Therapy: An Integrative Analysis Using Single-cell RNA and Bulk-RNA Sequencing Data

Abstract: Currently, a significant proportion of cancer patients do not benefit from programmed cell death-1 (PD-1)-targeted therapy. Overcoming drug resistance remains a challenge. In this study, single-cell RNA sequencing and bulk RNA sequencing data from samples collected before and after anti-PD-1 therapy were analyzed. Cell-cell interaction analyses were performed to determine the differences between pretreatment responders and nonresponders and the relative differences in changes from pretreatment to posttreatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 69 publications
(46 reference statements)
2
18
0
Order By: Relevance
“…Programmed cell death protein-1 and programmed cell death protein 1 ligand inhibitors can benefit patients with metastatic BC (Page et al, 2019). However, the immunotherapy of BC remains a major challenge to medical research (Jiang et al, 2021;Tabana et al, 2021). In the present study, we found that GPX1 is related to the immune infiltration of BC.…”
Section: Discussionsupporting
confidence: 50%
“…Programmed cell death protein-1 and programmed cell death protein 1 ligand inhibitors can benefit patients with metastatic BC (Page et al, 2019). However, the immunotherapy of BC remains a major challenge to medical research (Jiang et al, 2021;Tabana et al, 2021). In the present study, we found that GPX1 is related to the immune infiltration of BC.…”
Section: Discussionsupporting
confidence: 50%
“…Network centrality analysis suggested capillaries (in fetal and control/adult brains) and angiogenic capillaries (in pathological brains) as “senders” and venous ECs (in fetal, adult/control and pathological brains) as major “recipients” of MHC class II signaling and predicted elevated MHC class II signaling (predominantly in angiogenic capillaries) in brain pathologies (Figure 5q-t, Extended Data Figure 35). Notably, MHC class II signaling seems to be mediated mainly by APP and COPA ligands (and to a lesser extent by MIF ) and the CD74 receptor in AV-clusters across development, adulthood and disease (Extended Data Figure 35), and APP/COPA/MIF–CD74 have been described as ligand-receptor pairs between monocyte-derived macrophages and tumor ECs in human lung adenocarcinoma 70 and to be involved in antitumor immune response 83 .…”
Section: Resultsmentioning
confidence: 99%
“…Contrary to what was initially thought, recent data in the literature report anti-tumor reactivity of these exhausted CD8 + T cells and their increase in patients responding to anti-PD-1 therapy, suggesting a key role of these cells in the anti-tumor response. 27 , 28 …”
Section: Discussionmentioning
confidence: 99%